2018
DOI: 10.1002/epi4.12253
|View full text |Cite
|
Sign up to set email alerts
|

Cellular antiseizure mechanisms of everolimus in pediatric tuberous sclerosis complex, cortical dysplasia, and non–mTOR‐mediated etiologies

Abstract: SummaryThe present study was designed to examine the potential cellular antiseizure mechanisms of everolimus, a mechanistic target of rapamycin (mTOR) pathway blocker, in pediatric epilepsy cases. Cortical tissue samples obtained from pediatric patients (n = 11, ages 0.67–6.75 years) undergoing surgical resections for the treatment of their pharmacoresistant epilepsy were examined electrophysiologically in ex vivo slices. The cohort included mTOR‐mediated pathologies (tuberous sclerosis complex [TSC] and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…A recent study comparing ex vivo brain slices from TSC, HME and non‐mTOR pathology demonstrated robust anti‐seizure effects of everolimus (through reduction in glutamate receptor‐mediated excitatory activity after sustained exposure over time) in mTOR pathway‐related malformations (TSC and HME; Cepeda et al. ).…”
Section: What We Have Learned So Farmentioning
confidence: 99%
“…A recent study comparing ex vivo brain slices from TSC, HME and non‐mTOR pathology demonstrated robust anti‐seizure effects of everolimus (through reduction in glutamate receptor‐mediated excitatory activity after sustained exposure over time) in mTOR pathway‐related malformations (TSC and HME; Cepeda et al. ).…”
Section: What We Have Learned So Farmentioning
confidence: 99%
“…4-aminopyridine (4-AP) is a convulsant drug that blocks A-type K+ current, thereby facilitating neurotransmitter release at both excitatory and inhibitory synapses and has been shown to block fAHPs and increase AP halfwidth to dictate neuron firing rate and firing adaptation (Lorenzon et al, 1992, Faber et al, 2002, Guerrini et al, 2015) 10,42,29 . 4-AP has also been used in concert with a mg2+ free aCSF, high extracellular K+, GABA, glutamate, and inhibitory neurotransmitter blockers to promote and induce interictal and ictal activity in human epilepsy brain slice studies (Avoli et al,1991, Avoli et al, 1998, Cepeda et al, 2018, Chang et al, 2019, Guerrini et al, 2015 Levinson et al, 2020) 10,17,46,33,54,55 . However, to our knowledge, no substantial work has gone into how 4-AP influences L2/3 pyramidal neurons from epileptic acute slices.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, inactivation of TSC1 or - 2 leads to hyperactivation of the mTORC1 pathway, which upregulates normal cortical development and cellular proliferation and induces the development of tubers and SEGAs [ 10 ]. Additionally, abnormal functioning of mTOR pathway plays a crucial role in TSC-related epilepsy [ 11 , 12 ]. Therefore, mTOR inhibitors can be effective against both tumour growth and control of seizures [ 13 ].…”
Section: Reviewmentioning
confidence: 99%